Bandwidth allocation in high speed networks with multiple nested charge classes - Khalil, Ibrahim; Mohd Ali, Borhanuddin; Mukerjee, Malay R.
In integrated multimedia service networks, the charges for bandwidth would vary according to the nature of services provided. Maximization of revenue while maintaining QOS would be a goal for bandwidth allocation. Little attention has been paid to this aspect of network management. Here an effective allocation for multiple charge classes of customers is described.